Efektivitas Video Pembelajaran Berbasis Zenius.Net Dalam Meningkatkan Pemahaman Konsep Kimia Siswa - Safitri, Baiq Rina Amalia; Pahriah, Pahriah; Fuaddunnazmi, Muhammad (Hydrogen: Jurnal Kependidikan Kimia, 2022)
This research has a core objective, namely to find out the effectiveness of theÂ application of Zenius-based learning videos in improving students’Â understanding of chemical concepts. This research is included in the category ofÂ experimental type quantitative research. Meanwhile, the research method chosenÂ was One Group Pretest-Posttest Design, which means that only one researchÂ group was used. A total of 17 students were selected from class X and XI MAÂ Anshor Beber as the research population using saturated sampling technique orÂ population research. The data analysis technique used in this study combinesÂ descriptive data analysis for the measurement of the mean and inferentialÂ statistics for testing the significance of the t-test value. The significance of the Ngain value was tested using a t-test (paired samples t-test) and the results wereÂ used to interpret the extent of students’ understanding of chemical concepts. TheÂ average N-gain of students’ conceptual understanding after the application ofÂ Zenius-based learning videos is 0.7 with a medium category. The averageÂ understanding of students’ concepts after treatment (77) was proven to beÂ significantly greater than before being given treatment (34) based on the value ofÂ tÂ count = 28.8 which was greater than tcritical = 2.1 for dk = 15 with a p significanceÂ value of 0.000. Therefore, it can be concluded that zenius.net-based learningÂ videos are effective in increasing students’ understanding of concepts.